IMPLEMENTASI KEBIJAKAN PARTAI GOLKAR (STUDI KASUS TERPILIHNYA BUPATI DAIRI MENJADI KETUA GOLKAR KABUPATEN DAIRI) - Sigalingging, Elysabeth; Putra Erawan, I Ketut; Apriani, Kadek Dwita (Jurnal Nawala Politika, 2022)
The focus of this study aims to find out how the implementation of the Golkar Party's policies related to the election of the Dairi Regent to become the Golkar Chair of Dairi Regency in the IXth Regional Deliberation Session in 2020. Furthermore, this research is framed using the Rational Choice Theory from James S. Coleman to look at the preferences of actors to support individuals or groups with various goals. The research method used is a descriptive qualitative research method using primary data and secondary data, because in this study trying to describe the rationality factors that could lead to Airlangga Hartarto's support for Eddy Keleng Ate Berutu in the IXth Regional Deliberation Session of the Golkar Party of Dairi Regency in 2020. The result of this research is the existence of a discretionary policy letter from Airlangga Hartarto to Eddy Keleng Ate Berutu to achieve the desired goal in the election of the Chairman of the DPD II Golkar Party Dairi.